Pengembangan Media Pembelajaran Matematika Menggunakan Macromedia Flash 8 Pada Materi Bangun Ruang Sisi Lengkung Kelas IX: Pengembangan Media Pembelajaran Matematika Menggunakan Macromedia Flash 8 Pada Materi Bangun Ruang Sisi Lengkung Kelas IX - Aqilla Maudy Khalisa; Sari Herlina; Suripah Suripah; Fitriana Yolanda (Perspektif Pendidikan dan Keguruan, 2021)
This study aims to produce learning media using Macromedia Flash 8 on the curved side of solid figure material for class IX. This development model uses the model R & D, which has been modified according to the needs of the researcher into (1) problems and potential; (2) data collection; (3) product design; (4) validation design; (5) revision design; (6) product trial; (7) final production. The data collection technique used is a non-test technique in the form of a questionnaire. Data collection instrument utilized was a validation instrument in the form of a validation sheet, and a practical instrument in the form of a student response questionnaire sheet. The data analysis technique used is validation data analysis and practicality data of learning media. The results of the analysis of research validation by three validators obtained an average validation of learning media using a Likert scale of 88.56% which was included in the very valid category and the results of the questionnaire analysis of student responses by 12 students to learning media obtained an average of 86,73% is included in the very practical category. The conclusion of the study shows that learning media using Macromedia Flash 8 on the curved side of solid figure material has been tested to be very valid and very practical.